2020
DOI: 10.3389/fenvs.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Policy Recommendation on the Restriction on Amphibian Trade Toward the Republic of Korea

Abstract: Amphibian diseases and invasive amphibian species are both generally introduced through the wildlife trade, either for human consumption or for the pet trade. However, adequate regulations can prevent such introductions. In the Republic of Korea, the establishment of invasive Lithobates catesbeianus populations resulted in the alteration of native species' ecology and in an increase in Batrachochytrid load on local species. While not exemplified yet, the same risk arises from all species in the trade, some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, climate change may be expected to result in a northern shift of species range to follow adequate ecological requirements [ 89 ], however, and despite the unlikeliness of such dispersal to happen, the current range borders for all three species prevent such shift. Finally the species are under threat because of invasive species such as Lithobates catesbeianus [ 90 ] emerging diseases such as Batrachochytrids [ 91 , 92 , 93 ], and the synergy of both type of invasive and pathogens being increasingly released in the environment [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, climate change may be expected to result in a northern shift of species range to follow adequate ecological requirements [ 89 ], however, and despite the unlikeliness of such dispersal to happen, the current range borders for all three species prevent such shift. Finally the species are under threat because of invasive species such as Lithobates catesbeianus [ 90 ] emerging diseases such as Batrachochytrids [ 91 , 92 , 93 ], and the synergy of both type of invasive and pathogens being increasingly released in the environment [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ecosystems of the southern and western regions, on the other hand, are relatively less functional except some restricted regions along the south and west coast (including Jejudo Island) harboring a few unique species. Cautions are need for the growing amount of herpetofauna import 43 through the coasts. Since many studies revealed that herpetofauna of the Korean Peninsula are especially susceptible to climate change 28,[44][45][46] , the southern ecosystems need a particular conservation concern as habitats there will be disappeared sooner than later [45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…06/2019/NC-CP of Vietnam (2019). From the point of view of a recipient country of the trade such as the R Korea, where more than 85 anuran and 37 caudate species are imported in the pet trade ( Koo et al, 2020 ), 28 species such as Rana lessonae and Rana pipiens have been recently listed as “inflow-cautious organisms” (illustrating their potential as invasive species; R Korea; Ministry of Environment, 2020b ) and with efforts made to further limit the trade, now require special importation documentation ( Heo, 2008a ; Heo, 2008b ; Borzée et al, 2020a ). It is, however, necessary to acknowledge the benefit of amphibian farming locally for the pet trade in specific circumstances and under appropriate biosecurity measures ( Mattioli et al, 2006 ; Tensen, 2016 ).…”
Section: Regulation Of the Amphibian Pet Tradementioning
confidence: 99%